If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20(7u + -8v + 3w) = 0 (7u * 20 + -8v * 20 + 3w * 20) = 0 (140u + -160v + 60w) = 0 Solving 140u + -160v + 60w = 0 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '160v' to each side of the equation. 140u + -160v + 160v + 60w = 0 + 160v Combine like terms: -160v + 160v = 0 140u + 0 + 60w = 0 + 160v 140u + 60w = 0 + 160v Remove the zero: 140u + 60w = 160v Add '-60w' to each side of the equation. 140u + 60w + -60w = 160v + -60w Combine like terms: 60w + -60w = 0 140u + 0 = 160v + -60w 140u = 160v + -60w Divide each side by '140'. u = 1.142857143v + -0.4285714286w Simplifying u = 1.142857143v + -0.4285714286w
| 7z+2=-6 | | -7+2=6 | | 9x+16-6x=10-2x-19 | | 2p-3=p-5 | | 5a-16=25 | | v^2-10v+16= | | 4w-3x-y-5w+18x-7y= | | -6+[25+(-12)]=43 | | X^2+100+60-3x+30-4x=180 | | -6+[25+(-12)]=31 | | -13+2x=-52+13 | | -6+[25+(-12)]=7 | | -6+[25+(-12)]=19 | | 4=5+2x | | 5x+17-4x=-2-10 | | X/Y=7/11 | | 3x^2-(3m-2)x-(3m+1)=0 | | 1/3*1/3*1/3*1/3*a*a*b*b*c | | 5x-3y=106 | | 16+7yi=8x+i | | x-6=3(2x) | | f-5-3f=7 | | 2x+(x+1)=2 | | 2(4w+9)/4=-10 | | 5x/6-3/2=x/3 | | 0.5(7y+1)-3=8 | | 5(f-1)=25 | | 15m+2n-6m+8n= | | 15x^2+42x=9 | | (1/7)y-4=-18 | | 66=x/-2 | | 9-x=3-5x |